Interaction between Nickel Oxide and Support Promotes Selective Catalytic Reduction of NOx with C3H6. Issue 17 (26th July 2022) - Diao, Fan; Wang, Chizhong; Qiu, Lei; Yin, Yimeng; Zhao, Feilin; Chang, Huazhen
Abstract: Selective catalytic reduction of nitrogen oxides (NO x ) with C3 H6 (C3 H6 ‐SCR) was investigated over NiO catalysts supported on different metal‐oxides. A NiAlO x mixed oxide phase was formed over NiO/γ‐Al2 O3 catalyst, inducing an immediate interaction between NiO x and AlO x species. Such interaction resulted in a charge transfer from Ni to Al site and the formation of Ni species in high oxidation state. In comparison to other NiO‐loaded catalysts, NiO/γ‐Al2 O3 catalyst exhibited the highest NO x conversion at temperature higher than 450 °C, but a poor C3 H6 oxidation activity due to the decreased nucleophilicity for surface oxygen species. By temperature‐programed NO oxidation, it is indicated that nitrate species were rapidly formed and stably maintained at high temperature over NiO/γ‐Al2 O3 catalyst. In situ transient reactions further verified the Langmuir–Hinshelwood mechanism for C3 H6 ‐SCR, where both gaseous NO and C3 H6 were adsorbed and activated on catalyst surface and reacted to generate N2 . Due to the strong metal‐support interaction over NiO/γ‐Al2 O3 catalyst, both nitrate and C x H y O z intermediates were well preserved to attain high C3 H6 ‐SCR activity. Abstract : A strong metal‐support interaction between Ni and Al sites enhances the C3 H6 ‐SCR performance following L−H mechanism over NiO/γ‐Al2 O3 catalyst. Such interaction resulted in a charge transfer and the formation of Ni >2+ species over NiAlO x mixed oxide phase, which facilitated faster NO oxidation to adsorbed nitrates. Meanwhile, a decrease in charge density surface oxygen species hindered the overoxidation of C3 H6 .